Distributed maximum weight matching algorithm based on belief propagation - Yuan ZHANG (Tongxin xuebao)
The existing belief propagation based distributed MWM algorithm might have oscillating and uncertain phenomenon,which could result in the solving procedure not convergence or not converging to the correct solution.A new distributed MWM algorithm was proposed to fix the oscillating and uncertain phenomenon,in which the message calculation equations were modified.Simulation results show that the proposed algorithm outperforms existing algorithms and approaches the optimal performance.